Concepções de alfabetização e de sujeito em pesquisas no campo das Ciências da Linguagem. - Nogueira, Nívia Maria de Oliveira (2022)
This work aims to identify and analyze the conceptions of subject and literacy in academic productions, dissertations and theses, produced in the field of Language Sciences, with the intention of contributing to the debate about the role of the other in the acquisition of writing by the child. We chose to exclude other fields of study, such as Education, because we understand that there are already numerous studies addressing issues related to literacy and language acquisition written by children of early childhood education and initial grades, while in the field determined for this research, the occurrence in published academic papers is reduced, specifically in this last decade. Our particular interest was to contribute with reflections that could lead to a review of pedagogical practices, since we believe that the psychoanalytic theory about the constitution of the subject comes to break with the psychological, sociological and historical-cultural perspectives on language, from the notion of another (understood as the field of language or symbolic order). To this end, we start from the interactionist perspective in language acquisition, as formulated by Cláudia de Lemos, which is influenced by the studies of linguistics and psychoanalysis. More specifically, we will have as objectives: to investigate in the theoretical proposals used by the authors of the academic papers that conception of literacy and subject use; to analyze the conceptions used to think the subject in language; understand the relationship language and subject, depending on the conception assumed. Methodologically, we used triangulation by doing quantitative analysis and a documental observation (qualitative analysis) of the object of study. The analysis procedures were guided by principles and concepts derived from structural linguistics, particularly Saussure and Jakobson, and Freudian and Lacanian psychoanalysis. The theoretical path that gave consistency to this research allows us some considerations. The results point to the hegemony of conceptions related to the epistemic subject, of an learning focused on the construction of knowledge by the student, a legacy left by Emília Ferreiro, disciple of Piaget.